2017
DOI: 10.1016/j.jenvman.2017.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Risk aversion and willingness to pay for water quality: The case of non-farm rural residents

Abstract: Stated choice experiments are used to investigate the economic valuation of rural residents living in the province of Quebec for water quality improvements. In Quebec, rural residents played an important role in the setting of stricter environmental regulations. Unlike most stated choice experiments about the valuation of improvements in water quality, this study explicitly accounts for risk in the design and analysis of choice experiments. Risk in phosphorus and coliform reductions is introduced through a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Both certain and uncertain scenarios displayed the same average species target. In a CE exercise, Larue et al (2017), explore preferences for different levels of probable reductions in water quality pollution. They describe expected water quality outcomes using different distributions, with changing mean and with (or without) dispersion-signalling the presence (or absence) of uncertainty.…”
Section: The Effect Of Uncertainty In the Environmental Non-market Vamentioning
confidence: 99%
See 2 more Smart Citations
“…Both certain and uncertain scenarios displayed the same average species target. In a CE exercise, Larue et al (2017), explore preferences for different levels of probable reductions in water quality pollution. They describe expected water quality outcomes using different distributions, with changing mean and with (or without) dispersion-signalling the presence (or absence) of uncertainty.…”
Section: The Effect Of Uncertainty In the Environmental Non-market Vamentioning
confidence: 99%
“…In addition, these studies have often found highly heterogeneous responses to risk. In some results individuals were risk averse and tended to be willing to pay less for the scenario with uncertainty (Johansson 1989;Macmillan et al 1996;Isik 2006;Larue et al 2017), in others they were risk neutral and displayed no significantly different preferences for certain or uncertain scenarios (Koundouri et al 2014). One of the reasons for these heterogeneous results may be that the effect of risk on social preferences can differ depending on a variety of factors that were not generally controlled for.…”
Section: The Effect Of Uncertainty In the Environmental Non-market Vamentioning
confidence: 99%
See 1 more Smart Citation
“…Halkos & Matsiori (2016) examine(examined) the willingness to pay WTP to protect artificial lakes. Larue et al (2017) examined the economic assessment of rural residents living in the province of Quebec to improve water quality. Boyer et al (2016) examined the willingness to pay additional costs for reclaimed or recycled water.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result is different from the findings of Bravo-Vargas et al (2019) which stated that education, although brief, would increase awareness of controlling natural resources and the environment. Even Larue et al (2017) stated that highly educated residents were very willing to pay for pollution control. In line with the findings above, Gupta, M (2016) has found that education, income, and age played an important role in asking the community for environmental sustainability.…”
Section: Factors Affecting Rice Farming Wtps In the Suburban Areasmentioning
confidence: 99%